Analisis Faktor-Faktor yang Mempengaruhi Keputusan Petani dalam Memilih Benih padi Varietas Mekongga di Desa Matahoalu Kecamatan Uepai - Nur Annisa; La Karimuna; Mursal Junus (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to determine what factors influence the decision of farmers in selecting the seeds of the Mekongga variety. The research method used is multiple linear regression model. The number of respondents in this study were 30 respondent farmers with purposive sampling technique, with the provision that farmers used the seeds of the Mekongga variety..The results of this study indicate that factors such as age, production, land, and the number of familiy dependents have a significant influence on farmers' decisions in selecting the seeds of the Mekongga variety. so it can be concluded that these factors have an influence on farmers' decisions in choosing the seeds of the Mekongga variety an Factors that influence the decision in choosing Mekongga variety rice seeds in Matahoalu village, Uepai subdistrict, Konawe district The coefficient values obtained respectively for the age variable are 0.166, the production variable is 0.503, the land area variable is 0.239 and the number of family dependents variable is 0.269, indicating a larg Contribution coefficient of each variable in selecting Mekongga rice seed varieties.